Humoral immune responses to inactivated COVID-19 vaccine up to 1 year in children with chronic hepatitis B infection - Zhou, Yingzhi; Chen, Zhiwei; He, Yi; Peng, Xiaorong; Chang, Yunan; Tan, Aoxue; Li, Hu; Cai, Dachuan; Hu, Peng; Chen, Min; Peng, Mingli; Xu, Hongmei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Inactivated SARS-CoV-2 vaccination has recently been approved for children aged 3-17 years in China. However, data on long-term humoral responses to inactivated vaccines in children with chronic hepatitis B (CHB) are still limited. Methods: In this prospective observational study, CHB children after primary inactivated SARS-CoV-2 vaccines were recruited consecutively and followed up for 1 year. CHB adults from another cohort study (NCT05007665) were used as a control. The receptor-binding domain IgG antibody (anti-RBD-IgG), neutralizing antibody (NAb), neutralization against Omicron (BA2.12.1, BA.4 and BA.5), and memory B -cell (MBC) responses were evaluated. Results: Overall, 115 CHB children and 351 CHB adults were included in this analysis. The antibody titers decreased over the first 180 days and then plateaued up to 1 year in CHB children. However, lower and faster declines in antibody responses were observed in CHB adults. Interestingly, the seroprevalence of antibodies was still high after over 8 months in CHB children (anti-RBD-IgG [90%] and NAbs [83%]). However, neutralization against Omicron subvariants was significantly reduced in CHB children (-3.68-fold to -8.60-fold). Notably, neutralization against the BA.5 subvariant was obviously diminished in CHB children compared with adults. Moreover, CHB children had similar RBD-specific MBCs but higher RBD-specific atypical MBCs compared with adults. Conclusion: Inactivated vaccination could elicit more robust and durable antibody responses to the wild-type SARS-CoV-2 strain in CHB children than in CHB adults but showed inferior responses to Omicron subvariants (especially to the BA.5 strain). Hence, new Omicron-related or all-in-one vaccines are needed immediately for CHB children.